Analisis Penerapan Pendekatan Pembelajaran Mendalam pada Sekolah Menengah Kristen Swasta - Nalle, Maha Dewi Sabrina; Napitupulu, Bernard Wijaya (Universitas Pelita Harapan, 2026)
This article explores the implementation of deep learning approaches among teachers in a Christian private junior-senior high school. Using a quantitative survey with descriptive statistics, data were collected from 115 teachers through a Likert-scale questionnaire encompassing five indicators: (1) conceptual understanding of deep learning, (2) ability to plan instruction (LP/unit plan), (3) competence in designing assessments, (4) pedagogical competence in enacting deep learning in classroom practice, and (5) school support for teachers. The findings show that teachers generally report a positive level of competence on all indicators. They understand the basic framework of deep learning, design student-centred activities (inquiry, projects, problem-based learning), and begin to employ more meaningful, authentic assessments integrated with reflection. Teachers’ professional and collaborative attitudes emerge as a particular strength, reflected in their commitment to continuous improvement and willingness to share good practices. However, school support is perceived as adequate but not yet optimal, with persistent constraints in time, administrative workload, resources, and sustained guidance. These results indicate promising readiness for deep learning implementation, while highlighting the need for stronger institutional support and practical professional development.